2018
DOI: 10.14419/ijet.v7i3.21.17097
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Satisfaction of Food Services at the University Cafeteria: a Comparative Study Via PLS Approach

Abstract: This research investigated the effect of food quality, price fairness, staff performance, and ambience on students’ satisfaction of cafeteria food services by comparing responses from Universiti Malaysia Sabah (UMS), Malaysia with Mercu Buana University (MBU), Indonesia. Data was analysed using the Partial Least Squares (PLS) application in SmartPLS computer software version 2.0. Path coefficients from PLS results revealed ambience as the most significant predictor of students’ satisfaction of food services at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
5
1
Order By: Relevance
“…Employee attitude and student satisfaction Contrary to Chang and Suki's (2018) research where they found that staff performance is among the most significant attributes, in this study no direct effect of employee attitude on student satisfaction is found. At first sight, this result seems to support Chang et al's (2014) study in which they affirmed that students give less priority to staff performance.…”
Section: Impact Of Reliability On Sufficiency Of Services and Student...contrasting
confidence: 99%
See 4 more Smart Citations
“…Employee attitude and student satisfaction Contrary to Chang and Suki's (2018) research where they found that staff performance is among the most significant attributes, in this study no direct effect of employee attitude on student satisfaction is found. At first sight, this result seems to support Chang et al's (2014) study in which they affirmed that students give less priority to staff performance.…”
Section: Impact Of Reliability On Sufficiency Of Services and Student...contrasting
confidence: 99%
“…However, there are two-pronged comments from the literature in which some state significance of physical properties on customer satisfaction (e.g. Chang and Suki, 2018; Shanka and Taylor, 2005; Galabo, 2019; Smith et al , 2020), whereas, others reported no or few impact (e.g. Chang et al ., 2014; Liang and Zhang, 2009; Shanka and Taylor, 2005; Saglik et al ., 2014).…”
Section: Discussion and Contributionsmentioning
confidence: 99%
See 3 more Smart Citations